Christopher, an Asperger Syndrome Kid, Solved the Dog Murder Case in Novel The Curious Incident of the Dog in The Night-Time (2003) - Labiba, Darisa Taqiya; Agustina, Mia Fitria; Februasnyah, Rizki (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
The object of this study is The Curious Incident of the Dog in The Night-Time (2003), a novel that presents a story about a dog murder case that happened on the Mrs. Shears’s house lawn and Christopher, an Asperger Syndrome kid, tries to solve the case and disclose the murderer. The engaging topic which became the main discussion in this study is why Christopher with Asperger Syndrome can solve the dog murder incident in this novel. To analyze this topic, the researchers used the descriptive qualitative method. This study found that in favor of Christopher’s reasons to solve the dog murder case, Christopher has three reasons namely Christopher’s likes animals, especially dogs, Christopher’s desire to be a detective like Sherlock Holmes, and Christopher’s responsibility to find the murder since the dog belongs to his neighbor.